PENGARUH TRANSFORMATIONAL LEADERSHIP, DIGITAL TRANSFORMATION DAN WORK ENVIRONMENT TERHADAP EMPLOYEE PERFORMANCE MELALUI JOB SATISFACTION - Oktatia Putri, Adinda; Abadi, Ferryal (JURNAL LENTERA BISNIS, 2026)
This study examines the effects of Transformational Leadership, Digital Transformation, and Work Environment on Employee Performance, with Job Satisfaction serving as a mediating variable, among employees of conventional commercial banks in Jakarta. The research is grounded in the increasing demand for organizational performance improvement amid rapid digital transformation in the banking industry. A quantitative research design was applied using a survey method involving 135 respondents, and the data were analyzed through Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that Digital Transformation has a positive and significant impact on Job Satisfaction, whereas Transformational Leadership and Work Environment do not significantly influence Job Satisfaction. Furthermore, Transformational Leadership and Job Satisfaction demonstrate positive and significant effects on Employee Performance. However, Work Environment does not significantly affect Employee Performance through Job Satisfaction, indicating the absence of a mediating effect.These results highlight the strategic importance of strengthening transformational leadership practices and accelerating digital transformation initiatives to enhance employee satisfaction and performance in conventional banking institutions.